Giant insulinoma: report of a case and review of published reports - Ueda, Kazumitsu (Surg Case Rep, 2016)
BACKGROUND: Larger insulinomas are reportedly more likely to be malignant; however, their biological behavior has not been clearly elucidated. We here report the characteristics and treatment of a giant insulinoma with local invasion and lymph node metastasis. We also review published reports concerning the clinical features of giant insulinomas and comparing their grading with that of pancreatic neuroendocrine tumors. CASE PRESENTATION: A 71-year-old man was referred to our hospital for investigation of persistent hypoglycemia. On the current presentation, laboratory tests showed serum glucose, immunoreactive insulin, and C peptide concentrations of 45 mg/dL, 17.2 μIU/mL and 4.1 ng/mL, respectively. Dynamic magnetic resonance imaging showed a hypervascular tumor measuring 13.5 cm in the head of the pancreas. Computed tomography scanning demonstrated local invasion and lymph node involvement. He thus had Whipple’s triad, which is associated with malignant insulinoma. No distant metastases having been identified, pancreaticoduodenectomy was performed. Intraoperatively, three separate tumors were identified in the pancreatic head. Pathological examination showed all three tumors were pancreatic neuroendocrine tumors; the tumor cells in the largest mass were strongly immunoreactive for insulin. The Ki-67 index was 2–5% in most parts of the largest tumor and over 20% in the poorly differentiated areas. This tumor was classified as neuroendocrine carcinoma in accordance with the 2010 World Health Organization classification of pancreatic endocrine neoplasms. He remains free of evidence of recurrence 2 years postsurgery. A review of published reports indicated that giant insulinomas are more malignant than smaller ones, and metastatic disease is found on presentation in 56% of patients with giant insulinomas; however, we were unable to identify any correlation between grade of pancreatic neuroendocrine tumor and biological behavior of giant insulinomas. CONCLUSIONS: Giant insulinomas more frequently exhibit malignant behavior, such as local invasion, lymph node involvement, and liver metastasis, than smaller ones. However, there was no relationship between grade and rate of metastases or survival in this small case series. Identification of useful biological markers is necessary.